An analysis on fraud tendency of village government officials - Herlina Rahmawati Dewi; Mahmudi Mahmudi; Rafiq Maulana (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2021)
This research aims to analyze the influence of information asymmetry, religiosity, organizational culture, and regulatory enforcement toward fraud tendency of village government officials. This study employed a survey approach as the method to obtain data. Regression analysis was used to test the proposed hypotheses. From seventy-one respondents working as village government administrators in thirty-five villages in Magetan Regency, East Java Province, this study has found that information asymmetry, religiosity, organizational culture, and regulatory enforcement significantly affect the village government officials’ tendency to commit fraud.